Differences between COVID-19 and non-COVID-19 patients’ bloodstream infections: a single-center retrospective study - Keskin Sarıtaş, Çağla; Özsüt, Halit; Benli, Aysun; Başaran, Seniha (The Journal of Infection in Developing Countries, 2025)
Introduction: This study aimed to examine the differences between coronavirus disease 2019 (COVID-19) and non-COVID-19 patients with intensive care unit (ICU)-associated bloodstream infections (BSIs), in terms of epidemiological, clinical, microbiological, and outcome data. Methodology: All patients who were followed up in the ICU of a university hospital between 18 March 2020 and 18 April 2022, and who had developed ICU-acquired BSI, based on the study criteria, were selected and divided into 2 groups: COVID-19 and non-COVID-19. Descriptive statistics were used to analyze differences between the groups. Logistic regression analysis was applied to determine mortality risk factors in BSI patients. Results: 234 patients were treated for ICU-acquired BSI, 127 COVID-19 and 107 non-COVID-19. Respiratory sources were significantly more common in COVID-19 patients compared to non-COVID-19 patients (43.3% vs. 26%, p = < 0.01). Among the causative pathogens, Acinetobacter baumannii (24.4% vs. 5.6%, p ≤ 0.01) and Gram-negative multidrug-resistant (MDR) bacteria (81.7% vs. 61.7%, p = 0.020) were detected more frequently in COVID-19 patients than in non-COVID-19 patients. The duration of antibiotic use in the hospital before BSI was longer in COVID-19 patients than in non-COVID-19 patients, and this was also associated with BSI in which Gram-negative MDR bacteria were active (p = < 0.01). Survival times after BSI were shorter in COVID-19 patients than in non-COVID-19 patients (p = 0.032). Conclusions: We demonstrated that MDR microorganisms were prevalent in COVID-19 patients with ICU-acquired BSI, and this was partly due to antibiotic use in the hospital prior to BSI.